Rancang Bangun Aplikasi Penilaian Status Gizi Dan Penentuan Menu Makanan - Susanto, Johan Agus; Wibowo, Januar; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2012)
Nutrition is an important factor in human life. At the age of children, adolescents and adults, good nutrition is needed for growth, health and optimal stamina. Good nutrition can be obtained by consuming foods that are nutritionally balanced. But in times of growth and development, nutrition and food intake can not always be done perfectly, so the impact on excess weight and underweight. Therefore needed an application that can make an assessment of nutritional status and determination of food menu for children, adolescents and adults. Application assessment of the nutritional status and determination of food menu can make an assessment of nutritional status and determine food menu for children, adolescents and adults according to the daily calorie needs. With the weight input, height, age, gender, activity level and number of hours of sleep, a person can know the status of nutrition, ideal weight, daily calorie needs and menu suggestions which suit to the needs of daily calories. Assessment of nutritional status performed by using the Body Mass Index formula, while the calculation of caloric needs of adults carried out by using the method of Krause. The consultation result report contains the nutritional status, daily menu suggestions and shopping lists. This application made Web-based so that it can be accessed anywhere and anytime as long as users have Internet access and can use the internet Keywords: Methods Krause, Nutrition Status Assessment, Determination of Food Menu.